The Impact of Community Service Experience on the Undergraduate Students’ Learning Curve and Subsequent Changes of the Curriculum- A Quality Improvement Project at a Caribbean Medical University - Nauhria, Samal; Nauhria, Shreya; Derksen, Irene; Basu, Amitabha; Xantus, Gabor (Frontiers in Education, 2021)
Background: Community service learning seems to positively impact undergraduate medical students’ practical procedural and communications skills. Events like health fairs also strengthen the bond between healthcare providers and the wider community. Recognizing this mutually beneficial situation, national accreditation agencies and medical boards have recommended incorporating community-based learning in the core undergraduate curriculum. Our university is the first to probe medical students’ perceptions of community service in our region to the best of our knowledge. Objectives: We sought to analyze the experience of our students to improve the practical value of the curriculum. Methods: This was a qualitative survey interviewing medical students volunteering at a health fair in a Caribbean Island aimed to screen gross cardio-vascular and metabolic abnormalities in the native adult population. The focus group interviews were processed, transcribed and coded for thematic analyses by independent observers. Results: Overall, the students perceived CS as an opportunity to improve their clinical procedural and communications skills and to apply theoretical medical knowledge in practice to detect undiagnosed conditions like diabetes mellitus, hypertension and nutritional imbalance. Pedagogical implications: We have increased practical laboratory sessions by 15% in the new semester to improve our students’ practical skills. Conclusions: This is the first study that describes how community service may influence the individual learning curve of undergraduate medical students and may serve as a quality improvement tool to guide amendments to the curriculum. We opine that inter-agency, community-focused service promotes social, peer and active learning amongst undergraduate medical students.